Manual on the use of timber in coastal and river engineering - Crossman, Matt (Thomas Telford, 2004)
Designed to provide guidance on the principal issues surrounding the use of timber in coastal and river engineering. This manual provides an introduction to the use and properties of timber, a framework for responsible selection and procurement of timber materials, discussion of design and construction issues and maintenance practices, and more.
"This report also constitutes the joint Defra/Environment Agency Flood & Coastal Erosion Risk Management Research & Development Programme publication W5A-069"--Title page verso.
"Prepared by HR Wallingford and published on behalf of the Department of Trade and Industry and the Environment Agency"--Page v.
Keywords: Coastal engineering -- Great Britain -- Handbooks, manuals, etc.; River engineering -- Great Britain -- Handbooks, manuals, etc.; Building, Wooden -- Great Britain -- Handbooks, manuals, etc.; Timber.; Great Britain.; elektronické knihy; electronic books